Book review: Jo Dixon & Mike Stein (2005). Leaving Care: Throughcare and Aftercare in Scotland. London: Jessica Kingsley - Maxwell Smart (Scottish Journal of Residential Child Care)
It is good to come across a book about leaving care written in a Scottish context. Dixon and Stein's Leaving Care gives a 'warts and all' look at the experiences of young people leaving public care in three differing authorities in Scotland, referred to in the research as City, County and Shire. These authorities were markedly different in regards to demographics, social, economic, and geographical situations, and therefore reflect Scottish life more broadly, not just the circumstances for young people in the central belt of Scotland.